Electric current-assisted synthesis of ZIF-8 with stoichiometric metal and ligand precursors for CO2 adsorption. (February 2022) - Zhou, Yichen; Qiu, Jianhao; Ding, Meili; Zhang, Xiong-Fei; Yao, Jianfeng
Abstract: Zeolitic imidazolate framework-8 (ZIF-8) crystals were obtained by an electric current-assisted synthesis method with stoichiometric Zn 2+ and 2-methylimidazole precursors. The resulting ZIF-8-CS2 shows enhanced CO2 adsorption performance (31.2 cm 3 /g) with CO2 /N2 selectivity of 9 at 273 K, while ZIF-8 prepared without electric current assistance shows CO2 adsorption of 18.4 cm 3 /g and CO2 /N2 selectivity of 5. The increased CO2 adsorption ability is ascribed to the high specific surface area and total pore volume of ZIF-8-CS2. Highlights: Fine ZIF-8 powder (ZIF-8-CS) was obtained by electric current-assistance method. ZIF-8-CS owns bigger specific surface area and total pore volume. ZIF-8-CS shows better CO2 adsorption ability and CO2 /N2 adsorption selectivity.